18.6k views
1 vote
Hello does anyone know how to figure this out? - 3(4 + x) = x + 6

User Tgray
by
5.5k points

2 Answers

1 vote

Answer:

-4.5=x

Explanation:

First you would distribute the -3 to the 4 and x inside the parentheses

It would be -3 x 4= -12

Then -3 x X= -3x

So your equation would now be -12+ -3x = x + 6

Now you add 3x to the -3x to cancel it out and then add it to the x

So your equation now looks like -12=4x +6

Then you subtract 6 from the 6 to cancel it out and add it to the -12

Now your equation looks like -18=4x

Then you divide 4 from the 4x to cancel it out and then divide 4 from the -18

Finally you have -4.5=x

I'm unsure if this is correct but hopefully this helps :)

User MyNameIsCaleb
by
5.8k points
3 votes

Answer:

-4.5

Explanation:

-12-3x=x+6

-4x=18

x=-4.5

User Martin McCallion
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.